SEASONAL VARIATION OF TROPOSPHERIC OZONE AND THE IMPACT OF TRANSPORT OVER SYOWA STATION, ANTARCTICA - ムラヤマ, ショウヘイ; ヤマザキ, コウジ; アオキ, シュンジ; ナカザワ, タカキヨ; MURAYAMA, Shohei; YAMAZAKI, Koji; AOKI, Shuhji; NAKAZAWA, Takakiyo (National Institute of Polar Research, 1997)
P(論文) To interpret the height-dependent seasonal variations of the tropospheric O_3 mixing ratio observed over Syowa Station, Antarctica, atmospheric transport processes were examined using a 3-dimensional trajectory analysis with U. S. National Centers for Environmental Prediction (NCEP) data. Results from the analysis suggest that the seasonal O_3 variations are affected significantly by a combination of the following processes : (1) in the upper troposphere over Syowa, the downward transport of air rich in O_3 from the stratosphere is enhanced, while the transport of air poor in O_3 from lower levels is suppressed from summer to early autumn; (2) in the lower troposphere over Syowa, lower tropospheric air poor in O_3 is transported horizontally from lower latitudes and the transport of air with high O_3 mixing ratios from upper levels is reduced from late spring to early autumn; (3) vertical air mixing is enhanced in the Antarctic troposphere in cold seasons; and (4) in the middle troposphere, the upward transport of lower tropospheric air takes precedence over air transport from upper levels throughout the year except in summer. These transport processes are partly related so some meteorological features at southern high latitudes, such as the circumpolar trough and katabatic circulation. departmental bulletin paper